The Rule Against Perpetuities in Missouri, 1952-1983 - Harry W. Kroeger (Washington University Law Quarterly, 1984)
A little more than thirty years ago, I wrote for this Quarterly an article in which I discussed the effect in Missouri of a limitation void for remoteness upon other limitations contained in the same deed or will which, of themselves, were not remote. This Article is not intended to cover the same ground as the earlier article, though occasional references to it may be necessary to gain perspective. The focus at the present time is upon the happenings touching upon the rule against perpetuities since 1952. This focus requires a widening of scope beyond examination of questions concerning the effect of violation of the rule. It also dictates a narrowing of the period being examined which will undoubtedly entail omission of discussion of some important principles which were not dealt with by the cases during the period.
Keywords: Perpetuities; Remainders (Estates); Restraints on alienation; Reversion; Rule against perpetuities; Missouri